2008
DOI: 10.1097/pcc.0b013e31816c6f31
|View full text |Cite
|
Sign up to set email alerts
|

Serial blood lactate levels as a predictor of mortality in children after cardiopulmonary bypass surgery

Abstract: Lactime was a useful predictor of mortality in children undergoing repair or palliation of congenital cardiac defects under cardiopulmonary bypass. Initial and peak lactate levels had a poor positive predictive value for mortality. Lactime also was associated with the number of ventilator days and hospital days in those who survived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 19 publications
4
53
0
1
Order By: Relevance
“…Postoperative blood lactate levels are associated with outcome after both adult [1,2] and pediatric cardiac surgery [3,4]. Postcardiac surgery outcome is determined by the preoperative status of the patient, as well as by technical factors in the operating room and intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative blood lactate levels are associated with outcome after both adult [1,2] and pediatric cardiac surgery [3,4]. Postcardiac surgery outcome is determined by the preoperative status of the patient, as well as by technical factors in the operating room and intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kalyanaraman et al [24] showed that the initial and peak lactate are not significantly high in non-survivors of various types of cardiac surgery in children of various ages, however, they are not predictors of mortality. The time when the serum lactate level is above 2 mmol/L for more than 48 hours postoperatively, it predicts mortality in patients RACHS-1 (Risk Adjustment for Congenital Heart Surgery), with positive predictive value of 60%, sensitivity 50% and specificity of 98%.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of central venous oxygen sampling (Scv02, measured in %) per lactate (measured in mmol/L) had a better predictive value for major adverse events than each individual value measured alone (if the value of the ratio fell below 5 at any time after surgery, the positive predictive value for major adverse events was above 90%). The length of time it took for serum lactate levels to reach normal values was a useful predictor of mortality in children undergoing repair or palliation of CHD under CPB, while initial and peak lactate levels had a poor positive predictive value for mortality in that retrospective study (Kalyanaraman et al, 2008). Hyperlactatemia was described as the only predictor of persistent renal impairment at 48 hours at the time of admission to the intensive care unit was the admission blood lactate level (p = 0.018) (Duke et al, 1997).…”
Section: Post-pediatric Congenital Heart Disease Repairmentioning
confidence: 99%
“…According to the results of a retrospective review of children aged 0-21 years who had been admitted to a cardiac ICU, the length of time during which the lactate level remained greater than 2 mmol/L (18 mg/dL) was associated with the number of ventilator days and hospital days for the survivors. They all had surgery for CHD and required CPB (DeCampli & Burke, 2009;Kalyanaraman et al, 2008). The lactate level was also considered as being a risk factor for cerebral damage, which was defined as the development of seizures, movement disorders, developmental disorders, cerebral hemorrhage, infarction, hydrocephalus, or marked cerebral atrophy in children after they had undergone cardiac surgery (Trittenwein et al, 2003).…”
Section: Post-pediatric Congenital Heart Disease Repairmentioning
confidence: 99%